2018
DOI: 10.2298/vsp161201023t
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of depersonalization and suicidality in depressed patients

Abstract: Background/Aim. Depersonalization is considered to be the third leading symptom in psychiatric morbidity. The aim of this study was to investigate the correlation of depersonalization and different patterns of suicidal behaviour in patients suffering from depresssive disorder. Methods. The study included 119 depressed patients divided into two groups: the first group consisted of depressed patients with clinically manifested depersonalization according to the Cambridge Depresonalisation Scale presented score ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The impaired sense of agency exaggerates role of the Other's gaze in imaginary identification (blue route in Figure 1.f), leading to symptoms of depersonalization. As evidence, depressed individuals with depersonalization exhibit 8 times more often active suicidal ideation and 11 times more often passive suicidal ideation that those without depersonalization (Golubović et al, 2018). Desire for death, or passive suicidal ideation, is situated at the intersection between the Symbolic and the Real orders.…”
Section: Descriptive Model Of Suicide Ideation: a Lacanian Perspectivementioning
confidence: 95%
“…The impaired sense of agency exaggerates role of the Other's gaze in imaginary identification (blue route in Figure 1.f), leading to symptoms of depersonalization. As evidence, depressed individuals with depersonalization exhibit 8 times more often active suicidal ideation and 11 times more often passive suicidal ideation that those without depersonalization (Golubović et al, 2018). Desire for death, or passive suicidal ideation, is situated at the intersection between the Symbolic and the Real orders.…”
Section: Descriptive Model Of Suicide Ideation: a Lacanian Perspectivementioning
confidence: 95%
“…More broadly, future studies should also further assess memory recall abilities with regards to different kinds of memory content, as well as different memory systems, (e.g., episodic vs. semantic memory, seeFraiguero et al, 2021), or by contrasting DP with other mental health conditions known to impact memory processing such as anxiety and depression. For example, previous studies reported depersonalization symptomatology in severe cases of depression(Tošić Golubović, Žikić, Slavković, Nikolić, & Simonović, 2018). Given this relevant co-occurrence of altered self-narration and altered bodily feelings in dilated time experience, future research is needed to clarify what developmental trajectories the two aspects follow in diverse conditions presenting a common 'flattening' of time experience.Finally and importantly, while previous work focused on interoceptive processing in a static context, it would be important to assess it in relation to bodily movements and bodily actions, as humans need to move in order to survive.…”
mentioning
confidence: 99%